STRUKTUR KOMUNITAS BIVALVIA PADA PERAIRAN PANTAI DESA DULLAH KECAMATAN DULLAH UTARA KOTA TUAL MALUKU - Eddy, La; Suryani, Sanita; Manufury, Julia Deasy (Jurnal Pendidikan Matematika dan IPA, 2019)
Bivalves include sludge animals scattered in coastal waters with sand and mud substrate. This study was to determined the structure of bivalves communities in the coastal waters in Dullah Village, Tual City. This study was conducted from December 2016 until March 2017 using plot method measuring 1x1 meter. This study was result found 576 individuals consisting of 4 orders, 10 families, 14 genus, and 15 species. The largest species are Anadara antiquata with total of 118 individuals and the least species are Mytilus sp with 1 individual. The structure of the bivalvia community in the coastal waters of Dullah Village is less stable because of its moderate diversity so that dominance is low. In the absence of dominating species, the fairness of bivalves is high.